Marketized mentality and instrumental offending: the overlooked roles of noneconomic institutions and relative deprivation in individual level institutional anomie theory - Baron, Stephen W. (Journal of crime and justice, 2023)
This research examines the individual level extension to institutional anomie theory and explores the link between a marketized mentality and instrumental offending. Further, it investigates the direct roles that family, school and relative deprivation play in offending and probes their possible moderating impact on the relationship between a marketized mentality and illegal activities. Utilizing a street youth sample, the findings reveal that a marketized mentality in and of itself does not have a direct link to instrumental offending. Instead, the association between marketized mentality and offending emerges under conditions where individuals experience low family social control and high levels of relative deprivation. Relative deprivation, criminal peers, moral filters, prior offending, and low self-control also contribute directly to an increased probability of instrumental offending, while under certain conditions school social control decreases these probabilities. Findings are discussed, theoretical implications are outlined, and avenues for future research offered.